Nephrotic syndrome in a case of Rubinstein Taybi syndrome: a rare case report - Patro, Debasis; Agarwalla, Sunil Kumar; Ali, Nasreen; Sahoo, Manaswinee (International Journal of Research in Medical Sciences, 2017)
Rubinstein Taybi syndrome (RSTS) also known as Broad Thumb Hallux Syndrome characterized by distinct facial features with beaked or straight nose, short stature, moderate to severe intellectual disability, broad thumb and big toe. We report an interesting case of female child with history and examination suggestive of RSTS with Nephrotic syndrome. Investigation revealed presence of albumin in urine with hypercholesterolemia and hypoalbuminemia. Purpose of this case report is to highlight the distinctive presentation of this syndrome and to update the current state of knowledge.